NEUROLAW AND CHILD AGE LIMIT IN CRIMINAL RESPONSIBILITY - Saptama, Damai Alan; Putri, Aime Renata; Indradjaja, Nobella; Chamdani, Chamdani; Savage, Eileen (EQUALEGUM International Law Journal, 2024)
Background. Currently, research and reviews on the human brain are increasingly supported by continuously developing technological advancements. Thus, children's brain development is more easily comprehended along with the rapid growth of science. In criminal law, this supports the understanding of children's ability to control impulsive behavior. This research aimed to observe children's age limit in taking responsibility for crimes in the Indonesian law system by considering legal theories and science related to the cognitive neural system from the perspective of neurolaw. Research Method. In this research, the data is obtained from a literature study and analyzed conceptually based on legal regulation in Indonesia usually it’s namely normative legal research. Findings. The result of this research showed that in Indonesia, children can be imposed with criminal responsibility from the age of 12 until before they reach the age of 18. Meanwhile, from the perspective of neurolaw, the brain has not completely developed within that age range, and its shifts are reflected in human behavior. However, due to the gradual transition of brain development, it is impossible to determine an absolute age limit for brain maturity in the range of 12-17 years old, and thus children’s criminal cases must be reviewed individually. Therefore, the assistance or explanation of neural/psychiatric experts, besides legal experts, is required in handling children's criminal cases. Conclusion. Children can be charged with criminal responsibility from 12 to 18 years old, due to brain development shifts.